Joined-up services to tackle youth crime - Burnett, Ros (The British journal of criminology, 2004)
The ubiquitous theme of joined-up' services in UK government thinking is exemplified by recent reforms to the youth justice system in England and Wales. Previous research on multi-agency approaches has distinguished between benevolent' and conspiratorial' interpretations of joined-up criminal justice and has identified complexities in turning the rhetoric into reality. In line with conspiratorial perspectives, New Labour's changes to the youth justice system have been seen as evidence of further departure from welfare-based work, towards increased punitiveness and managerialism. This paper reports findings from an in-depth case-study of one youth offending team and its partnerships, exploring the realities of collaboration on three levels: core practice; specialist projects; and strategic management. It was found that the social work ethic has survived this overhaul of the youth justice system